A fully biodegradable composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202311576582.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-23
AI Technical Summary
该复合材料的比重较小,耐老化和耐热性优异,但其他功能组分含有较多的非降解成分,仍然对制品的最终分解造成一些不利影响
[0025]本发明提供了一种全生物降解复合材料,不包括非降解成分,其制备原料包括聚乳酸、聚乳酸-脂肪族二元酸腰果酚二元醇酯共聚物、脂肪族二元酸腰果酚二元醇酯、植物纤维和二环氧化腰果酚。本发明通过引入二环氧化腰果酚,可以显著加强聚乳酸、聚乳酸-脂肪族二元酸腰果酚二元醇酯共聚物、脂肪族二元酸腰果酚二元醇酯等与植物纤维之间的相互作用,增强相容性,从而提高复合材料的力学性能;通过引入聚乳酸-脂肪族二元酸腰果酚二元醇酯共聚物,可以进一步增加聚乳酸与脂肪族二元酸腰果酚二元醇酯间的相容性;通过引入脂肪族二元酸腰果酚二元醇酯,可以作为增韧组分,提升复合材料的韧性,与现有技术中常用的脂肪族二元酸二元醇酯相比,脂肪族二元酸腰果酚二元醇酯中引入了腰果酚,不仅降低了经济成本,还提升了可生物降解性。
Smart Images

Figure HDA0004567133680000011 
Figure HDA0004567133680000012 
Figure HDA0004567133680000021
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials and their preparation technology, specifically relating to a fully biodegradable composite material, its preparation method and application, and particularly to a polylactic acid / aliphatic dicarboxylic acid cashew phenol diol ester / polylactic acid grafted polyaliphatic dicarboxylic acid cashew phenol diol ester copolymer / plant fiber / diepoxide cashew phenol composite material, its preparation method and application. Background Technology
[0002] The widespread use of non-degradable polymer materials has generated massive amounts of plastic waste pollution, leading to significant development in biodegradable polymer materials in recent years. Among these, polylactic acid (PLA) exhibits high rigidity and strength, while polybutylene succinate (PBS), terephthalic acid-co-adipic acid-co-butanediol copolymer (PBAT), and poly(ε-caprolactone) (PCL) possess excellent flexibility. Plant fibers, as abundant renewable resources, are essentially natural polymers with hydroxyl groups, offering advantages such as low density, high strength, and low cost. Blending plant fibers with biodegradable polymer materials can produce fully biodegradable composite materials that combine strength and toughness. However, research has found poor compatibility between PLA, PBS / PBAT, and plant fibers, which hinders the improvement of the blend's mechanical properties and toughness. Furthermore, the relatively high price of PLA and PBS further limits their application as alternatives to non-degradable polymer materials. Therefore, finding a method to improve the compatibility between plant fibers and biodegradable polymer materials, enabling the final product to be fully biodegradable while possessing excellent comprehensive properties, is a pressing issue that needs to be addressed.
[0003] To achieve the goal of high-value utilization of plant fibers, chemical modification is performed based on their structural characteristics. Simultaneously, a polymer structure capable of reacting with the active groups of plant fibers is designed, which is highly feasible. Patent CN115536942A discloses a plant fiber-reinforced polypropylene composite material and its preparation method. This composition consists of homopolymer polypropylene, maleic anhydride-grafted polypropylene, high-temperature modified straw fiber, bamboo fiber, hollow glass microspheres, antioxidants, lubricants, and carbon black. Due to the presence of non-degradable components such as polypropylene, the final product cannot be completely decomposed.
[0004] Patent CN115434140A discloses a method for modifying the surface of plant fibers. The method involves sequentially treating plant fibers with acid and then with alkali to obtain acid-alkali pretreated plant fibers. These pretreated fibers are then impregnated with a coupling agent solution and cured to obtain silane-modified fibers. Further modification yields seed-layer zinc oxide-modified plant fibers. Finally, the seed-layer zinc oxide-modified fibers, an aqueous solution of zinc nitrate, and an aqueous solution of hexamethylenetetramine are mixed and subjected to a hydrothermal reaction to obtain zinc oxide nanorod-modified plant fibers. This method connects the plant fibers and zinc oxide nanorods through strong chemical bonds provided by the coupling agent, and the introduction of zinc oxide nanorods improves the interfacial compatibility between the plant fibers and polypropylene, as well as the mechanical properties of the composite material. However, this method has a lengthy processing procedure and is not easily implemented.
[0005] Patent CN114957935A discloses a polybutylene succinate-polylactic acid (PLA) composite material, the raw materials of which include: polybutylene succinate, polylactic acid, tributyl acetyl citrate, heat-resistant modified foamed plant fiber, aerogel intercalated clay composition, surface-modified tourmaline mixture, acid anhydride and / or acrylate graft-modified ethylene-vinyl alcohol copolymer, mineral powder, and additives. This composite material has a low specific gravity and excellent aging and heat resistance; however, the other functional components contain a relatively large amount of non-degradable components, which still have some adverse effects on the final decomposition of the product. Summary of the Invention
[0006] In view of this, the purpose of this invention is to provide a fully biodegradable composite material, its preparation method, and its application. The fully biodegradable composite material has low preparation cost, excellent mechanical properties and toughness, and can achieve complete degradation.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a fully biodegradable composite material, which is prepared by weight of 20-50 parts of polylactic acid, 10-50 parts of polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, 3-20 parts of aliphatic dicarboxylic acid cashew phenol diol ester, 5-30 parts of plant fiber, and 5-15 parts of diepoxidized cashew phenol.
[0009] Preferably, the fully biodegradable composite material is prepared by weight of 25-45 parts polylactic acid, 15-30 parts polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, 5-20 parts aliphatic dicarboxylic acid cashew phenol diol ester, 5-25 parts plant fiber, and 5-12 parts diepoxidized cashew phenol.
[0010] Preferably, the aliphatic dicarboxylic acid in the cashew phenol diol ester is selected from C... 2n dicarboxylic acid;
[0011] Where n is a positive integer from 1 to 5.
[0012] More preferably, the aliphatic dicarboxylic acid cashew phenol diol ester is selected from succinic acid and / or adipic acid, i.e., n=2 or 3.
[0013] Preferably, the mass ratio of polylactic acid to aliphatic dicarboxylic acid cashew phenol diol ester in the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer is (0.5-2):1.
[0014] Preferably, the number-average molecular weight of the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer is 10,000 to 70,000.
[0015] Preferably, the plant fiber is selected from any one or more of flax fiber, hemp fiber, ramie fiber, kenaf fiber, jute fiber, sisal fiber, or bamboo fiber.
[0016] Preferably, the plant fibers are pretreated with an alkaline solution.
[0017] Secondly, the present invention provides a method for preparing the above-mentioned fully biodegradable composite material, comprising the following steps:
[0018] Polylactic acid, polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, aliphatic dicarboxylic acid cashew phenol diol ester, plant fiber and diepoxidized cashew phenol were mixed in proportion and then extruded and injection molded to obtain a fully biodegradable composite material.
[0019] Preferably, the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer is prepared according to the following method:
[0020] Cashew phenol diol and aliphatic dicarboxylic acid are reacted in the presence of a first catalyst to obtain aliphatic dicarboxylic acid cashew phenol diol ester; aliphatic dicarboxylic acid cashew phenol diol ester and lactide are reacted in the presence of a second catalyst to obtain polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer.
[0021] Preferably, the first catalyst is selected from tetrabutyl titanate catalyst.
[0022] Preferably, the second catalyst is selected from stannous octoate catalysts.
[0023] Thirdly, the present invention provides a biodegradable product, including the fully biodegradable composite material involved in the above-mentioned technical solution.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0025] This invention provides a fully biodegradable composite material that does not include non-degradable components. The raw materials for its preparation include polylactic acid, polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, aliphatic dicarboxylic acid cashew phenol diol ester, plant fiber, and diepoxidized cashew phenol. This invention, by introducing diepoxidized cashew nut shell extract, can significantly enhance the interaction between polylactic acid, polylactic acid-aliphatic dicarboxylic acid cashew nut shell diol ester copolymer, and aliphatic dicarboxylic acid cashew nut shell diol ester with plant fibers, thereby improving compatibility and thus enhancing the mechanical properties of the composite material. Furthermore, the introduction of the polylactic acid-aliphatic dicarboxylic acid cashew nut shell diol ester copolymer can further increase the compatibility between polylactic acid and aliphatic dicarboxylic acid cashew nut shell diol ester. The introduction of aliphatic dicarboxylic acid cashew nut shell diol ester can also serve as a toughening component, improving the toughness of the composite material. Compared with commonly used aliphatic dicarboxylic acid diol esters in the prior art, the introduction of cashew nut shell extract into aliphatic dicarboxylic acid cashew nut shell diol ester not only reduces economic costs but also improves biodegradability.
[0026] Tests showed that the tensile strength of the fully biodegradable composite material provided by this invention is not less than 43 MPa and the elongation at break is not less than 105%. Attached Figure Description
[0027] Figure 1 The infrared spectra of cashew phenol and diepoxidized cashew phenol in Example 1;
[0028] Figure 2 The 1H NMR spectrum of cashew phenol in Example 1;
[0029] Figure 3 The image shows the 1H NMR spectrum of the dicyclooxygenated cashew phenol from Example 1. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0031] To address the problems of poor compatibility between plant fibers and biodegradable polymer materials and poor overall mechanical properties of the resulting composite materials in existing technologies, this invention provides a fully biodegradable composite material, prepared by weight from 20-50 parts of polylactic acid, 10-50 parts of polylactic acid-aliphatic dicarboxylic acid cashew nut glycol ester copolymer, 3-20 parts of aliphatic dicarboxylic acid cashew nut glycol ester, 5-30 parts of plant fiber, and 5-15 parts of diepoxidized cashew nut glycol.
[0032] In this invention, the fully biodegradable composite material comprises 20 to 50 parts by weight of polylactic acid, more preferably 25 to 45 parts. The polylactic acid provides the basis for the biodegradability of the fully biodegradable composite material. This invention does not impose any particular restrictions on the source of the polylactic acid; any commercially available product is acceptable.
[0033] In this invention, the fully biodegradable composite material comprises, by weight, 3-20 parts of aliphatic dicarboxylic acid cashew phenol diol ester, more preferably 5-20 parts. In this invention, the aliphatic dicarboxylic acid cashew phenol diol ester, compared to commonly used aliphatic dicarboxylic acid diol esters in the prior art, introduces cashew phenol, which not only reduces economic costs but also improves biodegradability. Simultaneously, the aliphatic dicarboxylic acid cashew phenol diol ester can serve as a toughening component, enhancing the toughness of the composite material and thus improving its overall performance. In this invention, the aliphatic dicarboxylic acid in the aliphatic dicarboxylic acid cashew phenol diol ester is selected from C... 2n The aliphatic dicarboxylic acid is a dicarboxylic acid; wherein n is a positive integer from 1 to 5, and can be 1, 2, 3, 4, or 5. Further, the aliphatic dicarboxylic acid is selected from succinic acid and / or adipic acid, i.e., n = 2 or 3. In some embodiments of the present invention, the aliphatic dicarboxylic acid cashew phenol diol ester is preferably succinic acid cashew phenol diol ester and / or adipic acid cashew phenol diol ester. The aliphatic dicarboxylic acid cashew phenol diol ester is preferably obtained by reacting an aliphatic dicarboxylic acid (i.e., succinic acid or adipic acid) with a cashew phenol diol.
[0034] In this invention, the fully biodegradable composite material comprises, by weight, 10-50 parts of a polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer, more preferably 15-30 parts. The introduction of the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer in this invention increases the compatibility between polylactic acid and aliphatic dicarboxylic acid cashew phenol diol ester, which is beneficial to improving the overall performance of the composite material. In this invention, the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer is obtained by polymerizing polylactic acid and aliphatic dicarboxylic acid cashew phenol diol ester, wherein the ratio of polylactic acid to aliphatic dicarboxylic acid cashew phenol diol ester is (0.5-2):1; the number average molecular weight of the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer is generally 10,000-70,000, specifically within the ranges of 10,000-30,000, 30,000-50,000, and 50,000-70,000.
[0035] In this invention, the fully biodegradable composite material comprises 5-30 parts by weight of plant fiber, more preferably 5-25 parts. The introduction of plant fiber can improve the strength of the composite material, increase the bio-based content, and effectively reduce costs. In this invention, the plant fiber is selected from any one or more of flax fiber, hemp fiber, ramie fiber, kenaf fiber, jute fiber, sisal fiber, or bamboo fiber. In some embodiments of the invention, it is preferable to pretreat the plant fiber with an alkaline solution to modify some of the hydroxyl groups on the surface of the plant fiber into sodium alkoxides, thereby disrupting the hydrogen bonding and crystalline structure between fiber molecular chains; simultaneously, the structures of lignin, pectin, and waxes are also destroyed, making the fiber structure looser and increasing the surface roughness. The loose fiber structure facilitates the mixing of different fibers, further chemical grafting modification of the fibers, and uniform dispersion of the fibers in the polymer matrix. The rough fiber surface also helps improve the interfacial bonding force between the plant fiber and the polymer material. The preferred mass / volume ratio of plant fiber to alkaline solution is (0.125–1):1 mL / g, more preferably (0.25–0.5):1 mL / g, and the preferred alkaline solution concentration is 3–5 wt%, more preferably 4 wt%. The alkaline solution pretreatment preferably involves soaking the plant fiber in the alkaline solution for 6–24 hours, more preferably 10–15 hours. In some embodiments of the present invention, after soaking, the plant fiber is preferably pulverized to a fiber length of 2–5 mm.
[0036] In this invention, the fully biodegradable composite material comprises 5-15 parts by weight of cardiolipin diepoxide, more preferably 5-12 parts. By introducing cardiolipin diepoxide, this invention significantly enhances the interaction between polylactic acid, polylactic acid-aliphatic dicarboxylic acid cardiolipin diol ester copolymer, aliphatic dicarboxylic acid cardiolipin diol ester, etc., and plant fibers, thereby improving compatibility and ultimately enhancing the mechanical properties of the composite material. This invention does not impose any particular restrictions on the source of cardiolipin diepoxide; it can be purchased commercially or prepared using methods well-known to those skilled in the art.
[0037] The fully biodegradable composite material provided by this invention is prepared from raw materials that do not contain non-degradable components, thus achieving full biodegradability. Furthermore, tests have shown that the tensile strength of the fully biodegradable composite material provided by this invention is not less than 43 MPa, and the elongation at break is not less than 105%, indicating that it possesses excellent comprehensive performance.
[0038] This invention also provides a method for preparing the above-mentioned fully biodegradable composite material, comprising the following steps:
[0039] Polylactic acid, polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, aliphatic dicarboxylic acid cashew phenol diol ester, plant fiber and diepoxidized cashew phenol were mixed in proportion and then extruded and injection molded to obtain a fully biodegradable composite material.
[0040] In this invention, the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer is preferably prepared according to the following method:
[0041] Cashew phenol diol and aliphatic dicarboxylic acid are reacted in the presence of a first catalyst to obtain aliphatic dicarboxylic acid cashew phenol diol ester; aliphatic dicarboxylic acid cashew phenol diol ester and lactide are reacted in the presence of a second catalyst to obtain polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer.
[0042] In some embodiments of the present invention, the cashew phenol diol and the aliphatic diacid are subjected to a polycondensation reaction at a molar ratio of (1-1.2):1, in the presence of a first catalyst, preferably tetrabutyl titanate catalyst, at 200°C or higher and a pressure of 0.2-2 kPa for 1-3 hours to obtain an aliphatic diacid cashew phenol diol ester. Then, the aliphatic diacid cashew phenol diol ester and lactide are reacted at a mass ratio of (0.5-2):1, in the presence of a second catalyst, preferably stannous octoate catalyst, at 150°C or higher and a pressure of atmospheric pressure for 1-3 hours to obtain a polylactic acid-aliphatic diacid cashew phenol diol ester copolymer.
[0043] In this invention, the diepoxidized cashew nut alcohol is preferably reacted with epichlorohydrin at 80–90°C for 1–2 hours in the presence of sodium hydroxide as a catalyst. The molar ratio of epichlorohydrin to cashew nut alcohol is (2–3):1, and the molar ratio of sodium hydroxide to cashew nut alcohol is (1.5–2):1. The reaction product is washed and separated to obtain diepoxidized cashew nut alcohol.
[0044] According to the present invention, after separately preparing polylactic acid-aliphatic dicarboxylic acid cashew nut glycol ester copolymer, aliphatic dicarboxylic acid cashew nut glycol ester, and diepoxidized cashew nut glycol, the polylactic acid-aliphatic dicarboxylic acid cashew nut glycol ester copolymer, aliphatic dicarboxylic acid cashew nut glycol ester, plant fiber, and diepoxidized cashew nut glycol are mixed in proportion. The mixing is preferably carried out in a high-speed mixer at a stirring rate of 100–300 rpm for 1–3 minutes. After uniform mixing, the resulting premix is preferably melt-granulated in a twin-screw extruder. In some embodiments of the present invention, the temperature of the twin-screw extruder is preferably set to 140–160–180–180–180–80–175°C. After melt granulation, the resulting product is preferably injection-molded at a temperature of 180–200°C.
[0045] The preparation method of the above-mentioned fully biodegradable composite material provided by the present invention is simple, easy to implement, and conducive to large-scale production.
[0046] The present invention also provides a biodegradable product, which includes the fully biodegradable composite material involved in the above technical solution.
[0047] To further illustrate the present invention, the following embodiments provide a detailed description. The experimental materials used in the following embodiments of the present invention are all commercially available products.
[0048] Example 1
[0049] This embodiment provides a fully biodegradable composite material, the preparation method of which is as follows:
[0050] (1) Preparation of epoxidized cashew nut shell phenol and cashew nut shell diol: Cashew nut shell phenol (658 mmol), epichlorohydrin (1316 mmol), and sodium hydroxide (1316 mmol) were mixed in a 500 mL three-necked flask equipped with a mechanical stirrer. The mixture was heated at 90 °C for 1.5 h, and then washed with a large amount of distilled water (1000 mL × 2, i.e., 1000 mL of distilled water each time, for a total of 2 washes). Finally, the epoxidized cashew nut shell phenol product was separated by funnel and evaporated under vacuum at 80 °C.
[0051] Epoxidized cashew nut alcohol was hydrolyzed by heating in the presence of dilute sulfuric acid at 90°C for 1 hour. The volume concentration of the dilute sulfuric acid was 30%, and the volume / mass ratio of dilute sulfuric acid to epoxidized cashew nut alcohol was 0.25 mL / g. After separation and removal of acid from the reaction product, cashew nut alcohol diol was obtained.
[0052] Cashew nut glycol was reacted with epichlorohydrin at 90°C for 2 hours in the presence of sodium hydroxide as a catalyst. The molar ratio of epichlorohydrin to cashew nut glycol was 3:1, and the molar ratio of sodium hydroxide to cashew nut glycol was 2:1. After washing and separation, the reaction product yielded cashew nut glycol diepoxide.
[0053] (2) Pretreatment of flax fiber: Soak 500g of flax fiber in 2L of 5wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 2mm long pieces.
[0054] (3) Synthesis of PLA-b-PCS-b-PLA copolymer: By bulk polymerization, 3.6 kg of cashew phenol diol, 1.2 kg of succinic acid, and 50 g of tetrabutyl titanate catalyst were added to a 10 L reactor. The reactor was heated to make the materials melted. The reaction was carried out under a pressure of 200 Pa while removing the by-product water. After 2 hours, the cashew phenol diol ester (PCS) macromolecular initiator was synthesized.
[0055] 2.8 kg of lactide and 10 g of stannous octoate catalyst were added to the reactor, and the reaction was continued for 1 hour to synthesize PLA-b-PCS-b-PLA copolymer. The molecular weight of the prepared PLA-b-PCS-b-PLA copolymer was 10,000 to 20,000.
[0056] (4) Preparation of PLA / PCS / PLA-b-PCS-b-PLA / Flax Fiber / Diepoxidized Cashew Phenol Composite Material: The PLA:PCS:PLA-b-PCS-b-PLA:Flax Fiber:Diepoxidized Cashew Phenol was fed in a mass fraction of 40:20:5:25:10. The material was then passed through a high-speed mixer (200 rpm, 2 min), a twin-screw extruder, and an injection molding machine to form a composite material. The temperature of the twin-screw extruder was set to 140-160-180-180-180-80-175℃, and the injection temperature was 180℃.
[0057] The mechanical properties of the composite material obtained above were tested according to GB / T 1040.2. The results showed that the tensile strength of the composite material was 48 MPa and the elongation at break was 120%.
[0058] Infrared spectroscopy was performed on the aforementioned cashew phenol and diepoxidized cashew phenol, and the results are as follows: Figure 1 As shown, compared to cashew phenol, the diepoxy cashew phenol spectrum contains epoxy groups.
[0059] The above-mentioned cashew phenol and diepoxidized cashew phenol were subjected to 1H NMR spectroscopy, and the results are as follows: Figure 2 and 3 As shown in the figure, the comparison reveals the presence of epoxy structures at 4.0–4.5 ppm.
[0060] Comparative Example 1
[0061] This comparative example provides a composite material, the preparation method of which is as follows:
[0062] (1) Pretreatment of flax fiber: Soak 500g of flax fiber in 2L of 5wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 2mm long pieces.
[0063] (2) Preparation of PLA / PCS / Flax Fiber Composite Material: The material was fed in a ratio of PLA:PCS:flax fiber of 40:35:25 by mass fraction. It was then processed by a high-speed mixer, a twin-screw extruder, and an injection molding machine to form a composite material. The processing temperature was 180℃.
[0064] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 35 MPa and the elongation at break was 7.5%.
[0065] Comparative Example 2
[0066] This comparative example provides a composite material that differs from Example 1 only in that the composite material is a PLA / PCS / PLA-b-PCS-b-PLA / flax fiber composite material, which does not include diepoxidized cashew nut shell powder, and its preparation method is the same as in Example 1.
[0067] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 38 MPa and the elongation at break was 20%.
[0068] Comparative Example 3
[0069] This comparative example provides a composite material that differs from Example 1 only in that the composite material is a PLA / PCS / polybutylene succinate (PBS) / flax fiber / diepoxide cashew nut shell composite material, that is, polybutylene succinate (PBS) is used instead of PLA-b-PCS-b-PLA, and its preparation method is the same as in Example 1.
[0070] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 40 MPa and the elongation at break was 14%.
[0071] Example 2
[0072] This embodiment provides a fully biodegradable composite material, the preparation method of which is as follows:
[0073] (1) Preparation of epoxidized cashew nut shell phenol and cashew nut shell diol: Cashew nut shell phenol (658 mmol), epichlorohydrin (987 mmol), and sodium hydroxide (987 mmol) were mixed in a 500 mL three-necked flask equipped with a mechanical stirrer. The mixture was heated at 80 °C for 2 h, and then washed with a large amount of distilled water (1000 mL × 2, i.e., 1000 mL of distilled water each time, for a total of 2 washes). Finally, the epoxidized cashew nut shell phenol product was separated by funnel and evaporated under vacuum at 85 °C.
[0074] Epoxidized cashew nut alcohol was hydrolyzed by heating in the presence of dilute sulfuric acid at 80°C for 2.5 hours. The volume concentration of the dilute sulfuric acid was 5%, and the volume / mass ratio of dilute sulfuric acid to epoxidized cashew nut alcohol was 2 mL / g. After separation and removal of acid from the reaction product, cashew nut alcohol diol was obtained.
[0075] Cashew nut glycol was reacted with epichlorohydrin at 80°C for 3 hours in the presence of sodium hydroxide as a catalyst. The molar ratio of epichlorohydrin to cashew nut glycol was 2:1, and the molar ratio of sodium hydroxide to cashew nut glycol was 1.5:1. After washing and separation, the reaction product yielded cashew nut glycol diepoxide.
[0076] (2) Pretreatment of kenaf fiber: Soak 500g of kenaf fiber in 2L of 4wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 3mm long pieces.
[0077] (3) Synthesis of PLA-b-PCS-b-PLA copolymer: By bulk polymerization, 2.4 kg of cashew phenol diol, 0.8 kg of succinic acid, and 50 g of tetrabutyl titanate catalyst were added to a 10 L reactor. The reactor was heated to make the materials melted. The reaction was carried out under a pressure of 200 Pa while removing the by-product water. After 2 hours, the cashew phenol diol ester (PCS) macromolecular initiator was synthesized.
[0078] Then, 6.0 kg of lactide and 10 g of stannous octoate catalyst were added to the reactor, and the reaction was continued for 1 hour to synthesize PLA-b-PCS-b-PLA copolymer. The molecular weight of the prepared PLA-b-PBS-b-PLA copolymer was 30,000 to 50,000.
[0079] (4) Preparation of PLA / PCS / PLA-b-PCS-b-PLA / Jenner Fiber / Epoxidized Cashew Phenol Composite Material: PLA:PCS:PLA-b-PCS-b-PLA:Jenner Fiber:Epoxidized Cashew Phenol were fed in a mass fraction of 30:30:10:20:10 and passed through a high-speed mixer (100rpm, 3min), a twin-screw extruder, and an injection molding machine to form a composite material. The temperature of the twin-screw extruder was set to 140-160-180-180-180-80-175℃, and the injection temperature was 185℃.
[0080] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 44 MPa and the elongation at break was 128%.
[0081] Comparative Example 4
[0082] This comparative example provides a fully biodegradable composite material, the preparation method of which is as follows:
[0083] (1) Pretreatment of kenaf fiber: Soak 500g of kenaf fiber in 2L of 4wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 3mm long pieces.
[0084] (2) Preparation of PLA / PCS / Jenner fiber composite material: The PLA:PCS:Jenner fiber were fed in a mass fraction of 30:40:30 and passed through a high-speed mixer, a twin-screw extruder, and an injection molding machine to form a composite material. The processing temperature was 185℃.
[0085] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 28 MPa and the elongation at break was 2.8%.
[0086] Example 3
[0087] This embodiment provides a fully biodegradable composite material, the preparation method of which is as follows:
[0088] (1) Epoxidation of cashew nut shell: Cashew nut shell (658 mmol), epichlorohydrin (658 mmol), and sodium hydroxide (658 mmol) were mixed in a 500 mL three-necked flask equipped with a mechanical stirrer. The mixture was heated at 100 °C for 1 h, and then washed with a large amount of distilled water (1000 mL × 2, i.e., 1000 mL of distilled water each time, for a total of 2 washes). Finally, the epoxidized cashew nut shell product was separated by funnel and evaporated under vacuum at 90 °C.
[0089] Epoxidized cashew nut alcohol was hydrolyzed by heating in the presence of dilute sulfuric acid at 60°C for 3 hours. The volume concentration of the dilute sulfuric acid was 20%, and the volume / mass ratio of dilute sulfuric acid to epoxidized cashew nut alcohol was 1.5. After separation and acid removal, the reaction product yielded cashew nut alcohol diol.
[0090] Cashew nut shell alcohol (CDBO) was reacted with epichlorohydrin at 110°C for 1.5 hours in the presence of sodium hydroxide as a catalyst. The molar ratio of epichlorohydrin to CDBO was 1:1, and the molar ratio of sodium hydroxide to CDBO was 1.5:1. After washing and separation, the reaction product yielded diepoxidized cashew nut shell alcohol.
[0091] (2) Pretreatment of jute fiber: Soak 500g of jute fiber in 2L of 3wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 4mm long pieces.
[0092] (3) Synthesis of PLA-b-PCS-b-PLA copolymer: By bulk polymerization, 1.5 kg of cashew phenol diol, 0.5 kg of succinic acid, and 10 g of tetrabutyl titanate catalyst were added to a 10 L reactor. The reactor was heated to make the material melted. The reaction was carried out under a pressure of 2000 Pa while removing the by-product water. After 2 hours, the cashew phenol diol ester (PCS) macromolecular initiator was synthesized.
[0093] Then, 4.0 kg of lactide and 20 g of stannous octoate catalyst were added to the reactor, and the reaction was continued for 1 hour to synthesize PLA-b-PCS-b-PLA copolymer. The molecular weight of the prepared PLA-b-PCS-b-PLA copolymer was 50,000 to 70,000.
[0094] (4) Preparation of PLA / PCS / PLA-b-PCS-b-PLA / Jute Fiber / Epoxidized Cashew Phenol Composite Material: PLA:PCS:PLA-b-PCS-b-PLA:Jute Fiber:Epoxidized Cashew Phenol were fed in a mass fraction of 25:35:5:30:5 and passed through a high-speed mixer (300rpm, 1min), a twin-screw extruder, and an injection molding machine to form a composite material. The temperature of the twin-screw extruder was set to 140-160-180-180-180-80-175℃, and the injection temperature was 190℃.
[0095] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 43 MPa and the elongation at break was 106%.
[0096] Comparative Example 5
[0097] This comparative example provides a fully biodegradable composite material, the preparation method of which is as follows:
[0098] (1) Pretreatment of jute fiber. Soak 500g of jute fiber in 2L of 3wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 4mm long pieces;
[0099] (2) Preparation of PLA / PCS / jute fiber composite material. The PLA:PCS:jute fiber were fed in a mass fraction of 25:35:40 and passed through a high-speed mixer, a twin-screw extruder, and an injection molding machine to form the composite material. The processing temperature was 190℃.
[0100] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 29 MPa and the elongation at break was 27%.
[0101] Example 4
[0102] This embodiment provides a fully biodegradable composite material, the preparation method of which is as follows:
[0103] (1) Epoxidation of cashew nut shell: Cashew nut shell (658 mmol), epichlorohydrin (1974 mmol), and sodium hydroxide (987 mmol) were mixed in a 1000 mL three-necked flask equipped with a mechanical stirrer. The mixture was heated at 80 °C for 3 h, and then washed with a large amount of distilled water (1000 mL × 2, i.e., 1000 mL of distilled water each time, for a total of 2 washes). Finally, the epoxidized cashew nut shell product was separated by funnel and evaporated under vacuum at 90 °C.
[0104] Epoxidized cashew nut alcohol was hydrolyzed by heating in the presence of dilute sulfuric acid at 70°C for 0.5 hours. The volume concentration of the dilute sulfuric acid was 30%, and the volume / mass ratio of dilute sulfuric acid to epoxidized cashew nut alcohol was 2. After separation and acid removal, the reaction product yielded cashew nut alcohol diol.
[0105] Cashew nut shell alcohol (CDBO) was reacted with epichlorohydrin at 100°C for 2.5 hours in the presence of sodium hydroxide as a catalyst. The molar ratio of epichlorohydrin to CDBO was 2.5:1, and the molar ratio of sodium hydroxide to CDBO was 1:1. After washing and separation, the reaction product yielded diepoxidized CDBO.
[0106] (2) Pretreatment of bamboo fiber: Soak 500g of bamboo fiber in 2L of 5wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 1mm long pieces.
[0107] (3) Synthesis of PLA-b-PCA-b-PLA copolymer: By bulk polymerization, 3.2 kg of cashew phenol diol, 1.2 kg of adipic acid, and 20 g of tetrabutyl titanate catalyst were added to a 10 L reactor. The reactor was heated to make the materials melted. The reaction was carried out under a pressure of 800 Pa while removing the by-product water. After 2 hours, the cashew phenol diol ester (abbreviated as "PCA") macromolecular initiator was synthesized.
[0108] Then, 2.2 kg of lactide and 5 g of stannous octoate catalyst were added to the reactor, and the reaction was continued for 1 hour to synthesize PLA-b-PCA-b-PLA copolymer. The molecular weight of the prepared PLA-b-PCA-b-PLA copolymer was 36,000.
[0109] (4) Preparation of PLA / PCA / PLA-b-PCA-b-PLA / bamboo fiber / epoxidized cashew nut shell composite material: PLA:PCA:PLA-b-PCA-b-PLA:bamboo fiber:epoxidized cashew nut shell composite material was prepared by feeding the materials in a mass fraction of 50:10:5:30:5. The materials were then processed by a high-speed mixer (250 rpm, 2 min), a twin-screw extruder, and an injection molding machine to form the composite material. The temperature of the twin-screw extruder was set to 140-160-180-180-180-80-175℃, and the injection molding temperature was 175℃.
[0110] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 45 MPa and the elongation at break was 115%.
[0111] Comparative Example 6
[0112] (1) Pretreatment of bamboo fiber. Soak 500g of bamboo fiber in 2L of 5wt% NaOH dilute solution for 24h, take it out and dry it, and then crush it into 1mm long pieces;
[0113] (2) Preparation of PLA / PCA / bamboo fiber composite material: The material was fed in a ratio of PLA:PCA:bamboo fiber of 50:15:35 by mass, and then passed through a high-speed mixer, a twin-screw extruder, and an injection molding machine to form a molded material. The processing temperature was 175℃.
[0114] The mechanical properties of the obtained composite material were tested according to the method in Example 1. The results showed that the tensile strength of the composite material was 40 MPa and the elongation at break was 10%.
[0115] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A fully biodegradable composite material, characterized in that, It is prepared by weight of 20-50 parts of polylactic acid, 10-50 parts of polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, 3-20 parts of aliphatic dicarboxylic acid cashew phenol diol ester, 5-30 parts of plant fiber, and 5-15 parts of diepoxidized cashew phenol. The plant fibers are pretreated with an alkaline solution; The mass ratio of polylactic acid to aliphatic dicarboxylic acid cashew phenol diol ester in the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer is (0.5~2):1; the number average molecular weight of the polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer is 10,000~70,000. The polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer was prepared according to the following method: Cashew phenol diol and aliphatic dicarboxylic acid are reacted in the presence of a first catalyst to obtain aliphatic dicarboxylic acid cashew phenol diol ester; aliphatic dicarboxylic acid cashew phenol diol ester and lactide are reacted in the presence of a second catalyst to obtain polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer.
2. The fully biodegradable composite material according to claim 1, characterized in that, The fully biodegradable composite material is prepared by weight of 25-45 parts polylactic acid, 15-30 parts polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, 5-20 parts aliphatic dicarboxylic acid cashew phenol diol ester, 5-25 parts plant fiber, and 5-12 parts diepoxidized cashew phenol.
3. The fully biodegradable composite material according to claim 1 or 2, characterized in that, The aliphatic dicarboxylic acid cashew phenol diol ester is selected from C... 2n dicarboxylic acid; Where n is a positive integer from 1 to 5.
4. The fully biodegradable composite material according to claim 1 or 2, characterized in that, The plant fiber is selected from any one or more of flax fiber, hemp fiber, ramie fiber, kenaf fiber, jute fiber, sisal fiber, or bamboo fiber.
5. A method for preparing a fully biodegradable composite material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Polylactic acid, polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer, aliphatic dicarboxylic acid cashew phenol diol ester, plant fiber and diepoxidized cashew phenol were mixed in proportion and then extruded and injection molded to obtain a fully biodegradable composite material. The polylactic acid-aliphatic dicarboxylic acid cashew phenol diol copolymer was prepared according to the following method: Cashew phenol diol and aliphatic dicarboxylic acid are reacted in the presence of a first catalyst to obtain aliphatic dicarboxylic acid cashew phenol diol ester; aliphatic dicarboxylic acid cashew phenol diol ester and lactide are reacted in the presence of a second catalyst to obtain polylactic acid-aliphatic dicarboxylic acid cashew phenol diol ester copolymer.
6. The preparation method according to claim 5, characterized in that, The first catalyst is selected from tetrabutyl titanate catalyst; The second catalyst is selected from stannous octoate catalysts.
7. A biodegradable product, characterized in that, The fully biodegradable composite material included in any one of claims 1 to 4 or the fully biodegradable composite material prepared by the preparation method according to claim 5 or 6.
Citation Information
Patent Citations
Plant fiber reinforced polypropylene composite material and preparation method thereof
CN115536942A
Polylactic acid modified composite
CN109054318A
Composite plant fiber biodegradable material and preparation method thereof
CN112646336A
Modified tourmaline polylactic acid melt-blown material as well as preparation method and application thereof
CN115537964A
